Method for modeling obesity in mature rates of the Wistar line - Bushman, V. S.; Бушман, Вікторія Сергіївна (НУОЗ ім. і П. Л. Шупика, 2022)
Morphological studies of the male reproductive system are very relevant in modern life. This is especially true of male infertility, benign hyperplasia, and prostate cancer.
Спосіб моделювання ожиріння у статевозрілих щурів лінії Wistar